The effectiveness of Tai Chi for patients with mild cognitive impairment: a systematic review and meta−analysis - Shao, Xinxin; Xi, Yawei; Pan, Lijie; Li, Xinru; Lin, Qianxin; Tian, Keming; Wang, Rui; Gao, Yutong; Gao, Hainan; Tan, Zili; Zhu, Xiangyu (Frontiers in Neuroscience, 2024)
ObjectiveTo explore the effectiveness of Tai Chi on cognitive function in patients with mild cognitive impairment (MCI).MethodsAccording to the PRISMA guidelines, randomized controlled trial (RCT) literature on the efficacy of Tai Chi on MCI patients was searched in China National Knowledge Network (CNKI), China Biomedical Literature Database (CBM), Wanfang Data, China Scientific Journal Database (VIP), PubMed, Embase, Duxiu Database, Web of Science and Cochrane Library from their inception to April 2024. The risk of bias in each study was appraised using the Cochrane risk−of−bias tool using Revman 5.4. Random effect model or fixed effect model was used to compare the effects of Tai Chi and control conditions on baseline and post−intervention assessment of cognitive function. Meta−analysis was performed using Stata15.0 software.ResultsNine studies fulfilled the inclusion criteria. Tai Chi significantly improved Montreal Cognitive Assessment (MoCA, SMD, 1.43, p < 0.00001), Delayed Recall Test (DRT, SMD, 0.90, p < 0.00001), verbal fluency test (VFT, SMD, 0.40, p < 0.00001), and Trail Making Test (TMT, SDM, −0.69, p < 0.00001) in MCI patients. Subgroup analyses showed that 24-forms Tai Chi was more effective than 8-forms Tai Chi in improving MoCA (SMD, 1.89, p < 0.00001) and 10-forms Tai Chi was more effective than 24-forms Tai Chi in improving DRT (SMD, 1.53, p < 0.00001).ConclusionTai Chi improved cognitive function in MCI patients, and Tai Chi types might be the influence factor on Tai Chi improving the global cognitive function and memory function in MCI patients.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/.